The legality of implementing alternative punishments - Muhammad Husni, Ahmad; Muhammad Husni, Amin (Zes Rokman Resources, 2022)
In these days and with the increase in population, crimes increase day after day as a result of technological development. One may commit a crime as a result of ignorance and without intention. This may happen from people who know no crime and is not their job, but they may have been victims of bad companions, and they may find themselves thrown into prison between criminals from murderers and drug addicts, and this may produce negative effect and they may end up learning crime because of staying between criminals. These kinds of people must be given an opportunity to correct their behaviors in order not to become criminals. Here the problem of the study lies as after coming out from the prison we find that the person has become a professional in crime and bad habit and become deviated after being a good person benefitting the society with his mind and his effort, and with that he becomes a shame on his family and his relatives. Here the study proposes resorting to alternative punishments in courts by providing counselors from scholars and clerics to advise those who commit minor crimes. This can be done by counseling and preparing the criminals of minor crimes by educating them if they are not educated, or teaching them a particular profession, and by this they can become beneficial to the society. The study found that preparing an alternative punishment is a successful system and will help the person who commits crime unintentionally in himself and his family. And with this the alternative punishment will rehabilitate the person who has no intention to commit crime, and thus, the alternative punishment will become a reform and refinement instead of prison and torture. And it is left to the judge to determine the alternative punishment based on the type of crime, place of its commission, method of its commission, age of the criminal and the motive for its commission.